A sensitive method for the detection of mutagenic nitroarenes: construction of nitroreductase-overproducing derivatives of Salmonella typhimurium strains TA98 and TA100 - Watanabe, Masahiko; Ishidate, Motoi; Nohmi, Takehiko (Mutation Research/Environmental Mutagenesis and Related Subjects, 1989)
‘Classical nitroreductase’ is an enzyme involved in the intracellular metabolic activation of mutagenic nitroarenes. The nitroreductase gene of Salmonella typhimurium TA1538 was cloned into pBR322 and the plasmids harboring the gene were introduced into TA98 and TA100. The resulting strains (YG1021 and YG1026) had more than 50 times higher nitrofurazone-reductase activity than TA1538 containing pBR322, and were extremely sensitive to the mutagenic action of 2-nitrofluorene, 1-nitropyrene and 2-nitronaphthalene. These results indicate that the new strains permit the efficient detection of mutagenic nitroarenes.